Impact of global climate change on the living conditions of small indigenous peoples of the Russian Arctic - A. D. Gorlova (Проблемы постсоветского пространства, 2024)
The article studies the current problems of the indigenous peoples of the Russian Arctic in the context of global warming. The main existing threats include both food and infrastructure issues, as well as problems of economic activity and health care. Against the background of global warming associated with an increase in the average annual temperature, there is a high probability that the above problems will only intensify and significantly affect all life support systems of the indigenous peoples of the Russian Arctic. Special attention is given to existing public and private initiatives, as well as proposed methods of adaptation and mitigation of the effects of global warming on indigenous peoples, including support for traditional knowledge and practices, sustainable use of natural resources and infrastructure improvements.